Effects of Crude Extracts from Medicinal Herbs Rhazya stricta and Zingiber officinale on Growth and Proliferation of Human Brain Cancer Cell Line In Vitro. (22nd July 2014) - Elkady, Ayman I.; Hussein, Rania Abd El Hamid; Abu-Zinadah, Osama A.
Abstract : Hitherto, limited clinical impact has been achieved in the treatment of glioblastoma (GBMs). Although phytochemicals found in medicinal herbs can provide mankind with new therapeutic remedies, single agent intervention has failed to bring the expected outcome in clinical trials. Therefore, combinations of several agents at once are gaining increasing attractiveness. In the present study, we investigated the effects of crude alkaloid (CAERS) and flavonoid (CFEZO) extracts prepared from medicinal herbs, Rhazya stricta and Zingiber officinale, respectively, on the growth of human GBM cell line, U251. R. stricta and Z. officinale are traditionally used in folkloric medicine and have antioxidant, anticarcinogenic, and free radical scavenging properties. Combination of CAERS and CFEZO treatments synergistically suppressed proliferation and colony formation and effectively induced morphological and biochemical features of apoptosis in U251 cells. Apoptosis induction was mediated by release of mitochondrial cytochrome c, increased Bax : Bcl-2 ratio, enhanced activities of caspase-3 and -9, and PARP-1 cleavage. CAERS and CFEZO treatments decreased expression levels of nuclear NF- κ Bp65, survivin, XIAP, and cyclin D1 and increased expression level of p53, p21, and Noxa. These results suggest that combination of CAERS and CFEZO provides a useful foundation for studying and developing novel chemotherapeutic agents for the treatment of GBM.